Doenças de vírus e cavalos para citrus - Giacometti, D C (Revista Ceres, 1957)
In this paper the author calls the attention for the problem of the virus diseases of Citrus related to the rootstock. The psorosis is registered as the major Citrus disease of the Pera sweet orange in the Fluminense-Carioca section of Brazil. The exocortis disease of the Rangpur lime rootstock is considered a minor problem in this section, been reported as carrier of the virus of the Lima and Baia Cabula sweet oranges, the Dancy tangerine and willow leaf mandarin. The disease was not found on trees of Pera sweet oranges on the same rootstock. The xyloporosis is not a serious disease in this Citrus section. It is reported a new disorder on the Rangpur lime named “enrugamento do limão Cravo”; the author discusses de possibilities of the disorder to be xyloporosis or “stempitting”. The importance of the nucellar lines of Citrus for rootstock trials is emphasided over the certified trees with suggestion of inocculation with mild strains of tristeza virus.